Soil Fertility, Sugarcane Yield Affected by Limestone, Silicate, and Gypsum Application - Costa Crusciol, Carlos Alexandre [UNESP]; Rossato, Otavio Bagiotto [UNESP]; Foltran, Rodrigo [UNESP]; Martello, Jorge Martinelli [UNESP]; Costa do Nascimento, Carlos Antonio [UNESP] (Taylor & Francis Inc, 2017)
The aim of this study was to verify if the application of silicate or lime, in association with gypsum, on sugarcane residue can lead to amendment of subsurface soil acidity, increasing sugarcane yield and profitability. The treatments were: 1 - control (without application of amendments), 2 - gypsum, 3 - dolomitic limestone, 4 - silicate, 5 - dolomitic limestone + gypsum, and 6 - silicate + gypsum. The surface application of gypsum led to reduction in Al (aluminum) contents and Al saturation, and increase in Mg+2, Ca+2, K+, S-SO4-, and base saturation in deeper soil layers, as well as increased yield of stalks, sugar, trash, bagasse, and energy, and greater profit. The application of limestone and silicate, alone or in association with gypsum, amend soil acidity throughout the soil profile. It likewise leads to an increase in stalk, sugar, trash, bagasse, and energy yield, however, application of silicate in association with gypsum leads to the greatest profitability.
Keywords: Sacharum spp.; soil acidity correctives; soil properties; stalks; surface